Ecological Niche Modeling of Three Species of Stenella Dolphins in the Caribbean Basin, With Application to the Seaflower Biosphere Reserve - Barragán-Barrera, Dalia C.; do Amaral, Karina Bohrer; Chávez-Carreño, Paula Alejandra; Farías-Curtidor, Nohelia; Lancheros-Neva, Rocío; Botero-Acosta, Natalia; Bueno, Paula; Moreno, Ignacio Benites; Bolaños-Jiménez, Jaime; Bouveret, Laurent; Castelblanco-Martínez, Delma Nataly; Luksenburg, Jolanda A.; et al. (Frontiers in Marine Science, 2019)
Dolphins of the genus Stenella occur in pelagic waters of both tropical and warm-temperate oceans. Three species, the Atlantic spotted dolphin (Stenella frontalis), the pantropical spotted dolphin (S. attenuata), and the spinner dolphin (S. longirostris) are abundant worldwide, but in the Caribbean Basin they have been poorly studied and information on their distribution patterns is scarce. Specifically, in Colombia’s remote Seaflower Biosphere Reserve (SFBR) S. attenuata has been reported occasionally, but S. frontalis and S. longirostris have never been recorded before. To address this information gap, an ecological niche modeling approach was used to determine the potential distribution patterns of these three dolphin species in the region. Records of these species for the Caribbean Basin were compiled, including both published and unpublished data. Environmental information, including bathymetry, bathymetric slope, distance to shore, sea surface temperature, sea surface salinity, and chlorophyll-a concentration was gathered from public databases (MARSPEC and Bio-ORACLE) in raster format. The maximum entropy algorithm (Maxent) for modeling species’ geographic distributions with presence-only data was used. After filtering the data, 210 records of S. attenuata, 204 of S. frontalis, and 80 of S. longirostris were used to run models. The best configuration for each model was chosen based on the ΔAICc criterion. For all three species, the final ecological niche models returned AUC test values higher than 0.8, indicating satisfactory model performance. The resulting potential distribution maps suggested that areas closest to continental shorelines of the Caribbean Basin and surrounding islands had the highest environmental suitability for all species (>70%). All models reported high environmental suitability for S. attenuata and S. longirostris in the SFBR, mainly in the southernmost part surrounding San Andrés and Providence Archipelago. Assessment of niche overlap from the predictions of species distributions using the similarity statistic and pairwise map overlap indicated that S. frontalis and S. longirostris had niches slightly more similar in comparison to S. attenuata. As this was a first effort to fill a gap in our understanding of the distribution of species in the genus Stenella in the Caribbean Basin, further studies are necessary using both niche modeling and biological/ecological approaches.